Effects of different fertilizer application practices on newly reclaimed soil structure and its nutrient content (Bangladesh Journal of Botany, 2021)
Effects of organic fertilizer practice (OF), organic fertilizer combined with chemical fertilizer practice (OC), and conventional fertilization practice (CF) on soil structure were evaluated by combining micro and macro analyses in newly reclaimed cultivated land. Soil organic matter (SOM), cation exchange capacity (CEC), soil bulk density (BD), soil moisture content (SMC), and aggregate stability were also analyzed. The CF soil structure was mainly composed of moderately separated block and angular structures with the minimum SOM (7.08 g/kg) and the highest BD (1.40 g/cm3), and the pore type was mainly simple surface cracks. Compared with CF, OF and OC significantly increased SOM content by 59.3 and 29.6% (p < 0.05) and CEC by 13.5 and 5.2%, respectively. The newly reclaimed soil structure was improved to a moderately separated clump structure and a well-developed aggregated structure, and the number of composite accumulation pores gradually increased. Moreover, OF and OC were associated with higher mean weight diameter (MWD), geometric mean diameter (GMD) values, and lower BD and fractal dimension (D) values. The water-stable macroaggregates (R0.25) and the aggregate stability of newly reclaimed soil were significantly increased, with a stronger improvement observed under OF. These results confirm the benefits of OC and OF practices on the structural stability, water and fertilizer retention characteristics of newly reclaimed cultivated land, and will be conductive to improving the soil quality and achieving sustainable soil development.Bangladesh J. Bot. 50(3): 781-794, 2021 (September) Special